(untitled) (Eurasian Research Bulletin, 2023)
This article conducts an economic analysis of population employment in business entities to understand its significance in driving economic growth and stability. The study examines various factors influencing employment trends, including economic growth, technological advancements, education levels, and government policies. Through comprehensive data collection, econometric models, and case studies, the article presents key findings on labor market trends and discusses the implications of employment policies. The conclusion offers suggestions to enhance employment opportunities and foster inclusive growth in economies